Measuring Students' Attitudes towards Mathematics Learning: Rasch Model Analysis from Junior High Schools in Palu City - Sugita, Gandung; Anggraini, Anggraini; Nurhayadi, Nurhayadi (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study aims to analyze students' attitudes toward mathematics learning based on the five affective domain dimensions of Krathwohl: Receiving, Responding, Valuing, Organization, and Characterization. The research employed a quantitative approach using a survey method. Data were collected from 447 junior high school students in Palu City through questionnaires and analyzed using the Rasch Model to evaluate item quality and student ability across each attitude component. The results indicated that most students fell into the low to moderate attitude categories, with logit distributions concentrated below the average value. Item reliability across all components was in the very high category (≥0.96), indicating strong instrument consistency in measuring the targeted constructs, while person reliability in components such as Organization and Receiving remained relatively low. The Wright Map analysis revealed a mismatch between students' ability levels and the difficulty of certain items, particularly in components requiring value internalization. These findings underscore the importance of implementing instructional strategies that holistically foster students' affective development. The study recommends reflective, participatory, and contextual learning approaches to strengthen students' positive attitudes toward mathematics learning in a sustainable manner.